A Novel Germline SDHA Gene Mutation and Co-Occurring Somatic KIT Activating Mutation in a Patient With Pediatric Central Nervous System Germ Cell Tumor: Case Report - Yue, Xizan; Liu, Bo; Han, Tiantian; Luo, Ningning; Lu, Guanghua; Guo, Didi; Bu, Fanfeng; Wang, Guangyu (Frontiers in Oncology, 2022)
Central nervous system germ cell tumors (CNS GCTs) are a heterogeneous group of primary CNS tumors. GCTs are more common and mostly observed in pediatric and young adult patients. CNS GCTs are divided into germinomas and non-germinomatous germ cell tumors (NGGCTs), with different therapeutic strategies depending on diagnosis. Herein, we report a patient with pediatric central nervous system germinoma harboring a somatic KIT p.Y823D and a heterozygous germline SDHA p. T396Nfs*14 mutation detected by next generation sequencing. After surgery, the patient received chemotherapy (temozolomide + nedaplatin + etoposide). This is the first report of a Chinese pediatric patient with CNS GCT harboring concurrent germline SDHA and somatic KIT mutation, which enriches molecular profiles of CNS GCTs and provides more molecular evidence of clinical diagnosis and potential targeted therapy in CNS GCTs.